THE EFFECT OF ENGLISH SONGS ON TEACHING TENSES - Masriani Mery Rosmida Silalahi (Sean Institute, 2021)
This study was intended to prove that there is a significant effect of using English songs on teaching tenses through an experimental research. This study belonged to quantitative study. The population of this study was the students of SMP Budi Utomo Binjai, and 70 students were taken as samples. To prove the hypothesis, the writer applied the t-test formula. Then the result of the t-test calculation is 2,9455. After comparing the t-test value of the t-table for both 0,05 (5%) and 0,01 (1%) at level of significance, it is found that the t-test value is higher than both level of significance value (2,9455 > 1,9955, and 2,9455 > 2,6501). It clearly means that the English songs significantly affect on teaching tenses